Problem Based Learning Penerapan Model Problem Based Learning dalam Pembelajaran Teks Diskusi pada Peserta Didik Kelas 9 SMP N 3 Kendal Tahun Pelajaran 2022/2023 - Fita Dwi Damayanti; Raden Yusuf Sidiq Budiawan; Mukhlis - (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to describe the application of the Problem Based Learning model in learning Discussion Text in grade 9 students of SMP N 3 Kendal for the 2022/2023 academic year. This type of research is descriptive qualitative supported by quantitative (mixed) data. Data collection in this study was carried out using test and non-test techniques in the form of questionnaires, observations, interviews, and documentation. Data analysis in this study was carried out using triangulation techniques. Presentation of data in this study was carried out using formal and informal methods. The results in this study indicate that the Problem Based Learning model can be applied in Discussion Text learning for grade 9 students of SMP N 3 Kendal. Based on the results of tests, interviews, observations, and questionnaires, the Problem Based Learning model is able to increase students' understanding of Discussion Text learning materials, is able to improve students' critical thinking skills, is able to make students more active in the learning process, and can make the class atmosphere more enjoyable. more conducive.